Potential of a Biofertilizer to Control Peregrinus maidis (Hemiptera: Delphacidae), an Insect Vector of Maize Mosaic Alphanucleorhabdovirus - Alviar, Karen B.; Zarate, Jocelyn T.; Yap, Sheryl A.; Albez, Rickson C.; Barbin, Arabelle Izza (AGRIVITA Journal of Agricultural Science, 2025)
The use of biofertilizers in combination with synthetic fertilizer has been effective in managing the population of Peregrinus maidis. The impact of a biofertilizer was assessed through the response of P. maidis. Corn plants were planted in potted soil with four different treatments. Plant defensin expression was determined using semi-quantitative PCR analysis, while lugensin expression in insects was analyzed using two-step semi-quantitative RT-PCR. Defensin is shown to be expressed in corn upon insect infestation on both biofertilizer Mykoplus and a combination of urea and complete fertilizers. The plants treated with the combination of urea and complete fertilizer  had similar numbers of insects (25%) to plants treated with biofertilizer alone. It was worth noting that although female macropters preferred biofertilizer-treated plants for oviposition, their preference in plants treated with urea and complete biofertilizer is not significantly different. Interestingly, the corn plants treated with biofertilizer plus urea had a similar number of oviposited eggs among the treatments (P=0.8166). This research presents novel results as it explores the potential benefits of using biofertilizers as a biocontrol method to manage the population of insect vectors that transmit a viral phytopathogen affecting corn.